The power of the blood - Whyte, H. A. Maxwell (New Kensington, PA : Whtitaker House, 2005)
"Examines the biblical foundations of the shed blood of Jesus Christ, as well as its potential impact in the lives of today's Christians"--Provided by publisher.
Foreword by Stanley H. Frodsham -- Preface to the newly revised edition -- There is a fountain filled with blood -- Life is in the blood -- Atonement by the blood -- The blood speaks -- The Passover -- The scarlet thread -- The value of the blood -- Arise, my soul, arise -- How to plead the blood -- The blood and divine health -- The application of the blood -- Holy Spirit baptism and the blood -- Protection through the blood -- There is power in the blood -- The new birth and the blood -- Wonder-working power of the blood.
Includes bibliographical references.
Keywords: Jesus Christ -- Blood